Analisis Tingkat Kebugaran Jasmani Siswa SMP Negeri Satap di Wilayah Kepulauan Tanakeke Kabupaten Takalar - Ihsan, Andi (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2026)
Limited space, land, and school facilities and infrastructure are factors that contribute to the low level of physical fitness of students. This condition results in minimal physical activity, both in play activities and physical education learning, which ultimately can affect students' physical fitness and learning quality. This study aims to analyze the level of physical fitness of students at Satap Pulau Lantang Peo State Junior High School, Takalar Regency. The study used a quantitative descriptive approach with an ex post facto design. The research subjects were 31 students who served as both the population and the sample. Data collection was carried out through physical fitness tests and measurements using the Indonesian Physical Fitness Test (TKJI) published by the Ministry of Youth and Sports of the Republic of Indonesia. Data analysis was carried out using descriptive percentage analysis techniques. The results showed that 2 students (6.5%) were in the good physical fitness category, 8 (25.8%) were in the moderate category, 19 (61.3%) were in the poor category, and 2 (6.5%) were in the very poor category. Based on these findings, it can be concluded that the level of physical fitness of students at Satap Pulau Lantang Peo State Junior High School is in the poor category. The results of this study are expected to be input for the Department of Education and related stakeholders in formulating policies and strategies to improve the quality of physical education learning in schools